A CD99+ primary spinal central PNET in a pregnant patient- therapeutic concerns and issues. (4th May 2019) - Soni, Aayesha Jalaluddin; Modi, Girish; Soni, Zakiyya; Kotzen, Jeffrey; Soni, Zaheera; Goolab, Vinod
Abstract: Spinal tumours in pregnancy are rare. Spinal tumours account for only 10–15% of all primary central nervous system (CNS) tumours. Most spinal tumours in pregnant women have been described as meningiomas or vascular tumours. We present the unique case of a pregnant patient presenting with a CD 99+ primary spinal central PNET.